Intellectual Property: the State of the Art - Vaver, David (Victoria University of Wellington Law Review, 2001)
This is an address which was presented by Professor David Vaver at Victoria University of Wellington on 30 August 2000. Professor David Vaver was brought to New Zealand by the New Zealand Law Foundation as the Distinguished Visiting Fellow for 2000. This address is based on an inaugural lecture delivered on 17 May 2000, at the Gulbenkian Lecture Theatre, Faculty of Law, University of Oxford and published as "Intellectual Property: The State of the Art" (2000) 116 LQR 621. VUWLR is grateful to the Law Quarterly Review for allowing republication of this address.